Auxin signaling, transport, and regulation during adventitious root formation - Muhamed Adem; Lata Sharma; Gyan Singh Shekhawat; Martin Šafranek; Ján Jásik (Current Plant Biology)
Adventitious roots (ARs) are post-embryonic roots that develop from non-root organs. These roots are vital for plant survival and are crucial for the clonal reproduction of valuable horticultural and forestry species. Despite their significance, ARs remain poorly understood. Research has shown that AR initiation and growth involve combined effects of genetic factors, growth regulators, and environmental stimuli. Cellular and molecular investigations have identified three key requirements for a cell to become an AR progenitor: it must be situated next to vascular tissue, exhibit high transcriptional activity, and undergo a redetermination of cell fate towards AR competency. The development of ARs is largely controlled by the interplay between auxins and other plant growth regulators (PGRs), such as cytokinins, ethylene, and jasmonates. Notably, the establishment of auxin concentration gradients through directional flow is essential for activating cellular processes necessary for AR formation. Recent studies have highlighted the importance of auxin-responsive genes, AUXIN RESPONSE FACTORs (ARFs) and AUXIN/INDOLE-3-ACETIC ACID REPRESSORs (Aux/IAAs) that play crucial roles in mediating AR initiation and emergence. Nevertheless, complex interactions between auxins and other PGRs remain the most enigmatic aspect of AR development. This review highlights the multifaceted roles of auxin and other PGRs in AR initiation and development, including biosynthesis, polar auxin transport, and regulation at the transcriptional, proteomic, and metabolomic levels.